2014
DOI: 10.1186/1678-9199-20-24
|View full text |Cite
|
Sign up to set email alerts
|

Hump-nosed viper bite: an important but under-recognized cause of systemic envenoming

Abstract: Hump-nosed viper bites are common in the Indian subcontinent. In the past, hump-nosed vipers (Hypnale species) were considered moderately venomous snakes whose bites result mainly in local envenoming. However, a variety of severe local effects, hemostatic dysfunction, microangiopathic hemolysis, kidney injury and death have been reported following envenoming by Hypnale species. We systematically reviewed the medical literature on the epidemiology, toxin profile, diagnosis, and clinical, laboratory and postmort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…In our study, Russell's viper was the most common snake identified followed by HNP, and haemotoxic envenomation was the predominant type of envenomation, consistent with previously published reports. This finding merits attention because HNP has recently been identified as an important venomous snake in South India and Sri Lanka, responsible for venom-induced coagulopathy, and the currently available polyvalent ASV is ineffective against their envenomation 12 13…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Russell's viper was the most common snake identified followed by HNP, and haemotoxic envenomation was the predominant type of envenomation, consistent with previously published reports. This finding merits attention because HNP has recently been identified as an important venomous snake in South India and Sri Lanka, responsible for venom-induced coagulopathy, and the currently available polyvalent ASV is ineffective against their envenomation 12 13…”
Section: Discussionmentioning
confidence: 99%
“…Although coagulopathy is reported frequently pulmonary haemorrhage is an unusual manifestation of humpnosed viper bite [3,4]. Here we report a patient who developed pulmonary haemorrhage which was successfully treated with systemic steroids.…”
Section: Introductionmentioning
confidence: 86%
“…Clinical manifestations of local envenoming predominate during the early phase; the clinical manifestations include pain, swelling, tissue necrosis, and hemorrhagic blisters [ 4 ]. The commonest systemic manifestations include coagulopathy evidenced by spontaneous bleeding [ 3 ] and subclinical coagulopathy evidenced by altered coagulation profile [ 5 ] or features of thrombotic microangiopathy (TMA) [ 6 ]. Although the early reports from case series of patients with hump-nosed viper bites revealed a lack of systemic effects other than coagulopathy [ 7 ], it is now clearly recognized that hump-nosed viper bites can lead to a multitude of systemic envenoming features and even death [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the early reports from case series of patients with hump-nosed viper bites revealed a lack of systemic effects other than coagulopathy [ 7 ], it is now clearly recognized that hump-nosed viper bites can lead to a multitude of systemic envenoming features and even death [ 5 ]. Acute kidney injury was noted in up to 20% of cases in recent studies [ 5 ]. Neurological and cardiac effects are not well recognized in patients with hump-nosed viper bites and cardiac effects have been limited to transient electrocardiogram (ECG) changes according to the available literature [ 5 ].…”
Section: Introductionmentioning
confidence: 99%